Asymptotic Behavior of the Solutions of the Generalized Globally Modified Navier–Stokes Equations - Yonghong Duan; Xiaojuan Chai (Discrete Dynamics in Nature and Society)
The paper is concerned with the existence and the asymptotic behavior of solutions to a class of generalized Navier–Stokes equations, which generalises the so-called globally modified Navier–Stokes equations. The existence and uniqueness of solutions are proved under different assumptions on the dissipation and modification factors. For the asymptotic behavior of solutions, we prove the existence of global attractors in proper spaces. The results generalize some results derived in our previous work Ann. Polon. Math. 122(2):101–128(2019).